STEREOTIP IMAM DIOSESAN DALAM SEJARAH GEREJA KATOLIK INDONESIA - Ngutra, Seno (Fides et Ratio : Jurnal Teologi Kontekstual Seminari Tinggi St. Fransiskus Xaverius Ambon, 2018)
Diocesan Priest is a man who was ordained to be a Priest in the Catholic Church. The Diocesan Priest is the term which is attributed to the Priest who has been incardinated himself to a certain Diocese which belong to the Catholic Church. He commits to serve the people of God in the Diocese wherever the Bishop assigned him. Therefore, he promises to obey to the Bishop for the whole life as a priest. Doing his mission, sometimes he faces many challenges that can create a big problem in his priesthood. He sometimes feels a dilemma between doing his best in the service or facing some critics that  come  from the people who are living around him. In this context, a Diocesan Priest must remember that who has called him to be a priest, was Jesus Himself. Jesus is the Lord and Protector for him.The diocesan priest is a priest forever.